1971
DOI: 10.1007/bf01372828
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of iron and manganese chelates in calcareous soils and their effectiveness for plants

Abstract: SUMMARY The behaviour of the metal chelates M n -E D T A , M n -D T P A , M n -E D D H A , F e -E D T A , F e -D T P A and F e --E D D H A in calcareous soilsand their availability to plants were studied.The effectiveness of a m e t a l chelate was shown to depend on its stability, the fixation capacity in the soil and its toxicity to the plant. Incorporation of F e -D T P A into a framework of silica molecules prevents the fixation of F e -D T P A in the soil.F e -D T P A and F e -E D D H A cause a reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In general, Mn and Zn chelates present lower stability than do Fe chelates (Boxma and Groot, 1971) but it is necessary to carry out a complete chemical speciation of the chelates and complexes to predict their behaviour. Halvorson and Lindsay (1972) have developed computer programs to calculate the equilibrium levels of chelated metals in nutrient solutions and in soil systems, considering solid phases and the presence of oxides.…”
Section: +mentioning
confidence: 99%
“…In general, Mn and Zn chelates present lower stability than do Fe chelates (Boxma and Groot, 1971) but it is necessary to carry out a complete chemical speciation of the chelates and complexes to predict their behaviour. Halvorson and Lindsay (1972) have developed computer programs to calculate the equilibrium levels of chelated metals in nutrient solutions and in soil systems, considering solid phases and the presence of oxides.…”
Section: +mentioning
confidence: 99%
“…Seed coatings containing MnEDTA have been ineffective (3), but the chelate has been used successfully in foliar sprays (4,104,116). Norvell and Lindsay (102) reported that activity of Mn added to aerated soil suspensions as MnDTPA was lost rapidly, but applications of this chelate to calcareous soils have alleviated both Mn and Fe deficiencies in plants (13).…”
Section: Manganese Sourcesmentioning
confidence: 98%
“…The chelated Mn is readily displaced by Fe (acid soils) and by Ca (alkaline soils) and Mn deficiency in plants can be intensified (13,72,132). Even small amounts of MnEDTA banded near seed can injure seedlings (116).…”
Section: Manganese Sourcesmentioning
confidence: 99%
“…Synthetic chelates, such as DTPA (diethylene triamine pentaacetic acid), EDTA (ethylenediaminetetraacetic acid) and HEEDTA (hydroxylethyl ethylene diamine triacetic acid), are the most widely used sources of Mn in alkaline solution and calcareous soil 3–5 . However, the persistence of these compounds in the environment, along with their strong ability to complex heavy metals and dissolve phosphates, represents an environmental risk in aquatic systems and thus necessitates the search for low‐cost, biodegradable complexing agents 6 …”
Section: Introductionmentioning
confidence: 99%